(untitled) (The Pakistan Development Review, 2007)
Both human and natural environment are interlinked with each other dynamically and keep this relation stable within themselves and with each other. The existence of all living organism including human being depends on the interlinkages between the physical human environment and natural environment. Natural resources and physical environment form a basis for sustainable livelihood system, in which human needs are met in the short and long run [Dankelman (2001)]. Although economic growth is an explicit goal in nearly every nation, but a wide range of independent scientific research provides undeniable evidence that the growth of the global economy is not sustainable because it consumes many of the environmental services that strengthen the production of goods and services [e.g., Houghton, et al. (1996); Vitousek, et al. (1997)]. Environmental services refer to the various ways that the environment influences production- and indeed-supports most part of human existence [Costanza and Daly (1992)]. There is a growing understanding that the degradation of environment and growth of waste materials can reduce the productivity of natural resources, as when ozone accumulates in the troposphere and lowers crop yields. This increases the quantity of human capital required to produce a specified quantity of food. The addition of wastes also slows the rate at which natural capital can process the waste material, as when sewage reduces the ability of aquatic ecosystems to process organic materials [Ayres (1996)]. There is also an increasing understanding that “economic growth does not necessarily go hand-in-hand with growth in the well-being of people”. It reflects the rising discrepancy between rich and poor and between genders in most countries [Ayres (1996)].